The essence of leasing, rent : opportunities and advantages. - Gritsenko, О.; Sachenko, O.; Klimenko, O.; Vlasyuk, V. (Ways to Improve Construction Efficiency, 2019)
The article describes the methods of attracting major production assets during construction on the terms of lease or rent. The author define their legal and economic content, the main features, the essence of relations between the parties to the contract and the advantages of each methods. The development of leasing and rent services in the Ukrainian market is explored.